Study the extent and severity of the drainage and soil salinity problems in Butana distributary of Western Yamuna Canal (WYC) - SINGH, PRASHANT; MISHRA, ANIL KUMAR; SINGH, DHIRENDRA KUMAR; SINGH, MAN; JAISWAL, SMITA (Journal of Soil and Water Conservation, 2020)
Field investigations were carried out during May to November, 2016; to study the extent and severity of waterlogging and soil salinity in Butana distributary of Western Yamuna Canal. Soil samples were collected from 13 study points from four depths (0-30, 30-60 and 60-90, 90-120 cm) during May, June, August and November months. Soil physico-chemical characterization was done in the laboratory and EC, pH, SAR, ESP, FC, PWP, OM, BD, particle density, drainable porosity and hydraulic conductivity etc. were worked out. The pH ranged from 7.32 to 8.41 indicating high salinity which remained almost constant during post monsoon months. The soil salinity in month of May 2016 in five groups ranged from 0.98-1.91, 1.91-2.84, 2.84-3.77, 3.77-4.70, 4.70-5.63 dS/m and corresponding salt affected area varied from 317.68, 398.31, 162.27, 139.33 to 73.83 ha, respectively. In the months of June, the soil salinity decreased from 4.70-5.63 to 4.29-5.13 dS/m and the corresponding areas were 73.83 to 73.94 ha. The Exchangeable Sodium Percentage (ESP) varied from 15.46 to 24.42 during June 2016 which indicated alkaline soil. It is observed from the spatial variability map of the ground water table during the month of May 2016 that it varied from 2.10 to 2.20 m below ground level (b.g.l). The soil salinity in months of August and November ranged from 0.86-3.51 and 0.86-4.56 dS/m. It was concluded based on the observations that the area is under severe soil salinity due to persistent waterlogging. Elaborate subsurface drainage system network is required to ease out the drainage impairment. The spatial variability maps of Ec, pH, ESP and SAR have been developed and discussed.